Assessment of Development Results - Timor-Leste - United Nations Development Programme (United Nations, 2014)
This Assessment of Development Results (ADR) in Timor Leste was conducted by the Independent Evaluation Office (IEO) of the United Nations Development Programme (UNDP) in early 2012, towards the end of the 2009–2013 UNDP programme cycle with a view to contributing to the preparation of the new UNDP country programme and the UNDP component of the forthcoming United Nations Development Assistance Framework. The evaluation also included the 2003–2008 country programme.